Letramento digital: o celular como ferramenta pedagógica para o aprimoramento de habilidades de leitura de charges - Aline Cristiana Ferreira (2019)
Aware of the current reality of the frequent presence of smartphones in classrooms and the necessity to improve reading skills in the students, especially multimodal texts, this research is supported by the Bakhtinian theory which argues that reading is understanding and this happens from the reader / text interaction, and this interaction raises in the reader, who is an active element in this process, a response. This research presents a methodological proposal of a qualitative approach to the development of multimodal text reading skills, using the smartphone as a search tool for information that favors comprehension. The objective is the improvement of reading skills from the textual cartoon, exploring the smartphone as a technological tool of educational mediation. This research will be developed at the Dom Benevides State School in Mariana, MG, in a ninth-grade class, from the reading of cartoons with the aid of the smartphone to search for information that will help the students in understanding. The search for information is going to be recorded by the screen recorder application AZ Screen Recorder and from a diagnosis a teaching project is going to be created and developed aimed to help the students to read in a productive way. At the end, new data is going to be generated to be compared to those of the diagnosis, aiming to understand the effects of the teaching project in the search to analyze the reading performed by the students. The results show that the students improve the comprehension of the functioning of the journalistic sphere, they developed various skills necessary to read cartoons, genre that guided this research, and the internet that they didn’t have on the beginning of this research, they became more prepared users and willing to try new ways to get more information that will lead them to understand texts.